Yan regulates Lozenge during Drosophila eye development. - Behan, J.; Nichols, C.D.; Cheung, T.L.; Farlow, A.; Hogan, B.M.; Batterham, P.; Pollock, A. (Development genes and evolution, 2002)
The Drosophila eye offers an excellent opportunity to understand how general developmental processes are subtly altered to result in specific cell fates. Numerous transcription factors have been characterized in the developing eye; most of these are active in overlapping subsets of cells. Mechanisms used to regulate transcription factors act at many levels, and include competition for cognate binding sites, post translational modification, transcriptional regulation and cofactor availability. In undifferentiated cells of the larval eye imaginal disc, the transcriptional repressor Yan outcompetes the transcriptional activator Pointed for ETS binding sites on the prosperoenhancer. During differentiation, the Ras signaling cascade alters the Yan/Pointed dynamic through protein phosphorylation, effecting a developmental switch. In this way, Yan and Pointed are essential for prospero regulation. Hyperstable Yan (ACT) cannot be phosphorylated and blocks prospero expression. Lozenge is expressed in undifferentiated cells, and is required for prospero regulation. We sequenced the eye-specific enhancer of lozenge in three Drosophila species spanning 17 million years of evolution and found complete conservation of three ETS consensus binding sites. We show that lozengeexpression increases as cells differentiate, and that Yan (ACT) blocks this upregulation at the level of transcription. We find that expression of Lozenge via an alternate enhancer alters the temporal expression of Prospero, and is sufficient to rescue Prospero expression in the presence of Yan (ACT). These results suggest that Lozenge is involved in the Yan/Pointed dynamic in a Ras-dependent manner. We propose that upregulated Lozenge acts as a cofactor to alter Pointed affinity, by a mechanism that is recapitulated in mammalian development.